Comparison of Anxiety Level on Medical Skill Examination Between Students of Medical Faculty of Hang Tuah University Surabaya in 1st Semester Who Have Received Mental Health Tests During The Entrance Test with 3rd Semester Who Have Not - Martua, Edwin Timotius; Wendra, Sadya; Simon, Edward Imanuel (Oceana Biomedicina Journal, 2019)
Anxiety is an unpleasant feeling of insecure tension and fear that arises because it feels something will happen that is disappointing but the source is largely unaware by the person concerned. Various studies have shown a high frequency of anxiety symptoms in medical students.The aim of this study is knowing the comparison of the level of anxiety to the medical skills test between students of Medical Faculty of Hang Tuah University Surabaya in 1ST semester who have received mental health tests during the entrance test with 3RD semester who have not received a mental health test during the entrance test.This study was an observational analytic study with a cross-sectional study design. The sampling technique used in this study is stratified random sampling. The population in this study were the first and third semester students of the Medical Faculty of Hang Tuah University Surabaya in the 2017/2018 school year, while the samples taken were 374 students meeting the inclusion criteria, Assessment of anxiety levels was carried out using the Hamilton Rate Scale for Anxiety (HRSA) questionnaire.Mild anxiety levels are more numerous in first-semester students (75%) compared to third-semester students (50%), while moderate-to-severe anxiety levels are more numerous in third-semester students (40%) compared to first-semester students (12.5%) who have received mental health tests during the entrance test.This study concluded there is a difference of ansiety level on medical skill examination between students of medical faculty of Hang Tuah University Surabaya in 1st semester who have received mental health tests during the entrance test with 3rd semester who have not received a mental health test during the entrance test. Keywords: Anxiety level, medical skills test, mental health test